1. MIDDLE EAR DISEASES AND EFFICACY OF VENTILATION TUBE INSERTION FOR OTITIS MEDIA IN CHILDREN WITH CLEFT PALATE (Vietnam Journal of Community Medicine, 2025)
Objectives: Cleft palate is associated with middle ear diseases, but the magnitude of this problem is not generally well appreciated. This study aimed to describe the middle ear status and evaluate the results of ventilation tube insertion in children with cleft palate.Methods: A cross-sectional cohort study was conducted to investigate 78 patients with cleft palate (CP). These patients underwent otoscopy and tympanometry to assess middle ear status. When chronic otitis media with effusion (OME), recurrent otitis media, or atelectasis was diagnosed, ventilation tube insertion (VTI) and palatal repair were performed simultaneously. The study was carried out at Nghe An Obstetrics and Pediatrics Hospital between 2023 and 2024.Results: Middle ear diseases occurred in 60.26% of patients with Cleft palate, with the incidence of OME and atelectasis being 30.76% and 24.35%, respectively. Type B tympanograms were most frequently observed (66.23%). The rate of post-VTI otorrhea was 10.34%, while the rate of tube extrusion after 3 months was 8.66%.Conclusions: We assessed the efficacy of ventilation tube insertion (VTI) in eliminating otitis media with effusion (OME) in patients with Cleft palate undergoing palatal repair. The results indicated that VTI is effective in eliminating OME in these patients.
Keywords: Cleft palate; otitis media with effusion; recurrent otitis media; ventilation insertion